Суха очистка доменних газів як елемент енергоефективності технології виробництва чавуну - Семірягін, С.В.; Осипенко, В.В.; Бубунець, Ю.В. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to coverage of the usage of dry purification systems for technological waste gases of a blast furnace process for the cast iron production. The dry blast furnace gas purification system is one of the important factors in the energy efficiency of the blast furnace process of cast iron production. Modern gas purification equipment based on bag filter elements makes it possible to obtain significant environmental results, and, in addition, to increase the calorific value of flue gases. The dry gas purification system implemented by Scientific and Manufacturing Enterprise Dneproenergostal LLC using a blast furnace with a useful volume of 1066 m3 is based on the usage of the FRIR-550 bag filter combined into a unit of 9 sections operating in an autonomous mode. The total system capacity is up to 180 thousand m3/hour, while in operation (purification mode) there are 5 to 8 sections, and the remaining sections are in regeneration mode or hot standby. The temperature regime of the filter to a greater extent depends on the technological regime of the blast furnace operation. The temperature range of the flue gases is 80–280 °С, while the filter cloth has a working temperature range of 120–150 °С. In order to regulate and adjust the temperature, the blast furnace gas purification plant (GPP) has two control systems, namely a radiator cooler and a gas duct-cooler irrigated with water. The rate of temperature drop on the radiator cooler is 0.7 °C/m. Temperature drop due to water is carried out automatically according to thermocouples data. The explosion and fire safety of the GPP is ensured by the use of inert gases for the filter regeneration period, and the tightness – due to the implementation of the gateway dust discharge circuit through the intermediate hopper tank. An efficient dry flue gas purification system provides the reliability of the TPP (Thermal Power Plant) equipment of the blast furnace steam air duct installation, eliminating the condensation effects and abrasive effect of flue gas dust.